The Role of Leadership in Driving Digital Transformation in the South African Financial Services Sector - Ngxola, Nomonde (University of the Witwatersrand, Johannesburg, 2023)
The purpose of the research is to provide an all-encompassing definition of Digital Transformation (DT) amid a sea of definitions and propose drivers that leaders operating in the South African Financial Services Sector can use to drive Digital Transformation within their respective organisations, not only as a mere project but also being mindful of the personal influence their role as leaders has on the success of a DT process (Bordeaux, 2019). From a systematic review of 100 peer-reviewed articles, the literature suggests there are seven common and key drivers of the Digital Transformation process. These were identified as digital business strategy, a review or augmentation of the organisations business model, big data-driven processes, process automation, customer centricity, digital competency, and culture (Bhardwaj et al., 2013). The literature also reflects the influential role that leaders play in the DT process through their traits and abilities (Kaidalova, Sandkuhl & Seigerroth, 2018). A close examination was made of the evolution of leadership theories: The Great Man Theory being the starting point, was premised on the leader’s abilities resting solely upon leader themself, believed to be born with a set of traits and behaviour that automatically deemed them leadership worthy (Cherry, 2019). During this era, the notion of leader development and training was not given thought (Hartl & Hess, 2017). The leader was according to this theory born and carried their own innate talents and capabilities to lead devoid any form of development and advancing. The paper seeks to explore the evolution of leadership theories that evolved from the trait and behavioural theories to that of transformational leadership, which looks specifically at leaders in relation to their subordinates to the latest DT theories to test for similarities, plus outliers when considered with respect to the methodological finding Additionally, the research incorporated notable barriers to the digital transformation process as noted by the leaders that were interviewed in the study. Themes of digital denialism, deflation and discomfort surfaced and were explored at length. vi The study adopted an exploratory sequential mixed methods approach compromising of qualitative content analysis and thematic analysis of semi-structured interviews using creative methods of extraction. The population sampled consisted of a group of Chief Information Officers, Chief Technology Officers, and Digital Heads of Business.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digital Transformation; Financial services; Banking Sector; Leadership; Barriers; Leading organizations; Leadership theories; Digital Leadership; UCTD; SDG-8: Decent work and economic growth